The effectiveness of cognitive rehabilitation and physical exercise on locomotor movement skill of children with developmental coordination disorder - Ayoub Hashemi; Robabeh Rostami; Habib Hadianfard (Sport Sciences and Health Research)
Introduction: The purpose of this study was to evaluate the effectiveness of cognitive rehabilitation and physical exercise on locomotor movement skill of children with developmental coordination disorder.Martials and Methods: The present study is a quasi-experimental study with a pre-posttest design with a control group. Eighty boys aged 6-10 years (mean age: 8.68±1.2) were selected from primary school students in Shiraz using multi-stage cluster sampling method and were randomly divided into three experimental (TDCS, Physical exercises and Combined group) and control groups. Developmental Coordination Disorder Questionnaire (DCDQ7), Raven Intelligence Test and Movement Assessment Battery for Children (MABC-2) were used to screen children. The Ulrich Gross Motor Skills Development Test (TGMD-2) was used to assess locomotor movement skills. Experimental groups performed the interventions for 8 weeks (3 sessions per week and 45 min per session). Paired t-test and analysis of covariance were used to analyze the data.Results: The results showed that the locomotor movement skill score in the groups of cognitive rehabilitation, physical exercise and combined intervention from the pre-test to post-test stages increased significantly (P<0.05). While in the control group no significant difference was observed (P>0.05). The results also showed that locomotor movement skill in the combined groups and physical exercise in the post-test were significantly higher than the cognitive rehabilitation and control groups (P<005).Conclusion: Concomitant use of cognitive rehabilitation-related interventions with physical exercise is more effective in improving locomotor movement skill in children with developmental coordination disorders.